The Effect of Job Strain on Psychological Morbidity and Quality of Life in Military Hospital Nurses in Taiwan: A Follow-up Study - TZENG, Dong-sheng; CHUNG, Wei-ching; YANG, Chun-yuh (Industrial Health, 2013)
This study investigated changes in job strain in female nurses serving in a military hospital system being restructured and the effect of these changes on psychological morbidity and quality of life (QOL). Questionnaire surveys were sent twice to 618 nurses working in three military hospitals in southern Taiwan at the beginning and at follow up a half year later. A Job Content Questionnaire was used to divide subjects into high and low strain groups. The General Health Questionnaire and the WHO QOL Questionnaire were used to assess psychological morbidity and QOL. Four hundred eighteen nurses completed the study. Initially, the high strain group had a greater prevalence of psychological morbidity and lower QOL than the low strain group. At follow up, high strain group did not have a greater prevalence of psychological morbidity, though significant differences in QOL remained. Job control and social support directly affected the QOL (B=0.42, p<0.001; B=0.41, p=0.038, respectively) and the psychological demand affected directly on psychological morbidity (B=0.12, p<0.001). Job control and psychological demand are different aspects in job strain to impact the psychological morbidity and QOL in nurses working in military hospitals in Taiwan.